2011
DOI: 10.1370/afm.1287
|View full text |Cite
|
Sign up to set email alerts
|

Original and REGICOR Framingham Functions in a Nondiabetic Population of a Spanish Health Care Center: A Validation Study

Abstract: PURPOSE Risk functions can help general practitioners identify patients at high cardiovascular risk, but overprediction inevitably leads to a disproportionate number of patients being targeted for treatment. To assess predicted cardiovascular risk, we analyzed the 10-year performance of the original and REGICOR Framingham coronary risk functions in nondiabetic patients. METHODSOurs was a longitudinal, observational study of a retrospective cohort of patients observed for 10 years in primary care practices in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In order to correlate the CV-ZS with other validated cardiovascular risk scores, the Framingham and REGICOR (for Spanish population) scores were estimated according to the equation described by Wilson P.W. et al 57 and through the online calculator available at www.imim.cat/ofertadeserveis/software-public/regicor/?1 58 , respectively. Both scores include age, sex-adjusted cardiovascular risk variables (total cholesterol, HDL-C and SBP and DBP), and presence of diabetes and tobacco consumption (both variables collected using a questionnaire).…”
Section: Study Populationmentioning
confidence: 99%
“…In order to correlate the CV-ZS with other validated cardiovascular risk scores, the Framingham and REGICOR (for Spanish population) scores were estimated according to the equation described by Wilson P.W. et al 57 and through the online calculator available at www.imim.cat/ofertadeserveis/software-public/regicor/?1 58 , respectively. Both scores include age, sex-adjusted cardiovascular risk variables (total cholesterol, HDL-C and SBP and DBP), and presence of diabetes and tobacco consumption (both variables collected using a questionnaire).…”
Section: Study Populationmentioning
confidence: 99%
“…analyzed the 10-year performance of the original Framingham coronary risk functions in nondiabetic patients. 37 They reported the observed (PO,t=10=0.109) and predicted (PE,t=10=0.169) 10-year risk estimates in a table, as well as the total number of observed events (Ot=10=22). Hence, we have with …”
Section: Data Extraction and Estimating Unreported Results To Facilitate Meta-analysismentioning
confidence: 99%
“…[32][33][34] Moreover current most study's findings explain the rise of cardiovascular diseases risk factors in rural communities. 35 The study findings showed a minimal or fair level of agreement of 0.25 between FGRS and WHO/ISH score chart which is not acceptable in models prediction agreement by Cohen kappa due to models lack of discrimination capacity to fulfil the accuracy requirement of a test, a classifier or a model that requires the interrater reliability coefficient to be perfect at least 0.8 for the accurate agreement between used two models (FGRS and WHO/ISH score chart) to be both applied in Rwandan population. FGRS predicted 25.5% of the population to have elevated cardiovascular diseases absolute risk in coming 10 years (≥10%) while WHO/ISH score chart predicted only 4.6% of the population to have elevated risk of (≥10%) with a high predictable difference of 20.9% risk which underlined a suspect of under prediction of WHO/ISH score chart and Over prediction of FGRS.…”
Section: Discussionmentioning
confidence: 99%